Hubungan Media Sosial Tiktok Dengan Minat Beli Konsumen - 10080021140, Raihan Firjatullah Irvanianto; Zulfebriges (Bandung Conference Series: Communication Management, 2025)
Abstract. The development of digital technology has transformed the marketing landscape, making social media, especially TikTok, a primary platform that significantly influences consumer behavior. TikTok offers interactive, creative, and entertaining short-form videos, creating digital experiences capable of shaping consumer purchasing decisions. However, limited research specifically analyzes the relationship between TikTok content elements such as text, photos, audio, and video and consumer purchase intent. Therefore, this study aims to address this knowledge gap by evaluating how each TikTok content element contributes to purchase intent. This research tests the relationship between TikTok content elements and consumer purchase intent, focusing on the @hihihi_crop account. A quantitative correlational approach was used to measure the influence of content elements on aspects of purchase intent, including transactional, referential, preferential, and exploratory intent. Data were collected through a questionnaire distributed to 123 respondents who follow the TikTok account @hihihi_crop. The data were analyzed using Spearman Rank Correlation. The study results show that all TikTok content elements have a significant relationship with purchase intent, with video emerging as the most influential element, followed by audio, photo, and text. This study confirms that TikTok content elements represent an effective digital marketing strategy to increase product appeal and influence consumers’ purchasing decisions. Abstrak. Perkembangan teknologi digital telah mengubah lanskap pemasaran, menjadikan media sosial, terutama TikTok, sebagai platform utama yang memengaruhi perilaku konsumen secara signifikan. TikTok menawarkan format video pendek yang interaktif, kreatif, dan menghibur, menciptakan pengalaman digital yang mampu membentuk keputusan pembelian konsumen. Namun, masih sedikit penelitian yang secara spesifik menganalisis hubungan antara elemen konten TikTok, seperti teks, foto, audio, dan video, dengan minat beli konsumen. Oleh karena itu, penelitian ini dilakukan untuk mengisi kesenjangan pengetahuan dengan mengevaluasi bagaimana masing-masing elemen konten TikTok berkontribusi terhadap minat beli. Penelitian ini bertujuan menguji hubungan elemen konten TikTok dengan minat beli konsumen, khususnya pada akun @hihihi_crop. Pendekatan kuantitatif korelasional digunakan untuk mengukur pengaruh elemen konten terhadap aspek minat beli, meliputi minat transaksional, referensial, preferensial, serta eksploratif. Data dikumpulkan melalui penyebaran kuesioner kepada 123 responden, yang merupakan pengikut akun TikTok @hihihi_crop. Teknik analisis data menggunakan korelasi Rank Spearman. Hasil penelitian menunjukkan seluruh elemen konten TikTok memiliki hubungan signifikan dengan minat beli, dengan video sebagai elemen paling dominan. Penelitian ini menegaskan elemen konten TikTok merupakan strategi pemasaran digital efektif dalam meningkatkan daya tarik produk dan keputusan pembelian konsumen.